Exposure to news, economic crises in social communication And his future relationship towards the future - Maytham Falin Hussein, DR (lark, 2023)
during the current period, especially poor countries, including Iraq, and what we notice of the media's interest in the immediate coverage of these events, thinking and worrying about the future has become one of the things that occupy the mind or thinking of the public, so thinking about the future and prediction It has become something that prevails in all societies and peoples that are trying to find a place for themselves on the global map, and the problem of the current study and its objectives crystallize in the basic question: What is the relationship between the exposure of the Iraqi public to the news of economic crises through social networking sites and the characteristics of anxiety towards the future for them? The importance of studying the effects of news of economic crises through the new media, with the seriousness of its role at the present time, and it is considered a temporary study, as it studies the relationship of news of economic crises with social media with the level of anxiety towards the future. The study aims to identify the nature and patterns of exposure to news of economic crises on social networking sites, and to identify the levels of anxiety among Iraqis about these crises. The most important results of the study were an increase in the use of social networking sites to a degree of up to 90% between permanent and medium follow-up, and among the most important topics of the economic crisis are oil prices, approving the budget, forming a government, and wasting money.
Keywords: social networking sites, economic crises, anxiety for the future.